Het statuut van Brussel in geval van confederalisme - Hugues Dumont; Sébastien Van Drooghenbroeck (Brussels Studies, 2007)
This article looks into the future of Brussels in the hypothesis of Belgium’s move towards confederalism. After defining this term and making a distinction between its legal and political usage, the authors explore various scenarios that could lead from federalism to confederalism, showing that the latter is not a mere continuation of the former and that the path is strewn with heady questions. They then review the statuses that could be envisaged for Brussels in the hypothetical wake of such a move, and call for an interdisciplinary and citizen-based reflection in reaction to their analyses.